Effective Healthcare Worker-Patient Communication in Hong Kong Accident and Emergency Departments. Issue 2 (March 2015) - Slade, D; Chandler, E; Pun, J; Lam, M; Matthiessen, Cmim; Williams, G; Espindola, E; Veloso, Fod; Tsui, Kl; Tang, Syh; Tang, Ks
Introduction: This paper reports on research conducted within a Hong Kong (HK) accident and emergency department (AED), which investigated the effectiveness of health care worker-patient communication over the course of patients' journeys from triage to disposition. Methods: The research combined qualitative and quantitative ethnographic methods with linguistically-oriented discourse analysis of audiotaped interactions between patients and health care workers. It involved: (1) observations, (2) semi-structured interviews with management and health care workers, (3) surveys with AED staff, (4) audio-recordings of 10 patients' journeys, and (5) follow-up interviews with patients. Results: The paper described the typically complex communication networks involved in AED care. It then exemplified how certain communicative strategies, balancing the communication of medical knowledge with interpersonal communication, could be used to achieve positive healthcare outcomes. This was illustrated by a case study of one patient's journey through the AED, pinpointing health care workers' effective use of communication strategies, their effect on the patient's participation and subsequently the patient's understanding and evaluation of the care he received. Conclusion: The high stress nature of AEDs inevitably poses challenges to communication. The results of this study, however, strongly suggest a correlation between health care workers' use of effective, interpersonally sensitive communication strategies and positive patient outcomes. Health care worker-patient communication that effectively balances interpersonal communication with the communication of medical expertise is integral to ensuring patients' participation in, understanding of, and satisfaction with their healthcare. These communication strategies should be required components in health care worker communication training. (Hong Kong j.emerg.med. 2015;22:69-83)